2021
DOI: 10.1002/joc.7249
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced moisture transport associated with the interdecadal change in winter precipitation over Northwest China

Abstract: In this study, the interdecadal increase in winter precipitation in northwest China (NWC) since the late 1980s and the associated moisture flux transport are investigated. The results show that an interdecadal change in moisture flux transport also occurred in the late 1980s, resulting in anomalous moisture transport convergence over NWC. The examination of boundary moisture transport shows enhanced incoming net moisture flux transport over NWC after the late 1980s. The zonal and meridional components both pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Many previous studies have revealed that North Atlantic SST anomalies can trigger continental‐scale wave trains to affect the climate over downstream regions (e.g., Chen et al, 2022; Watanabe, 2004; Wu et al, 2011). Some recent works have found that the interdecadal transition in the phase of the North Atlantic‐related Eurasia (EU) pattern during the late 1980s plays a primary role in the interdecadal changes of moisture transportation, which in turn, contribute to the increased precipitation over northwest China after the late 1980s (Yin & Zhou, 2022; Zhou & Wu, 2015). The contemporaneous anomalous SSTs over the North Atlantic associated with the PIhf were examined for both P1 and P2 (Figure 6a,b).…”
Section: The Sptb Variations Related Ocean–atmosphere Anomaliesmentioning
confidence: 99%
“…Many previous studies have revealed that North Atlantic SST anomalies can trigger continental‐scale wave trains to affect the climate over downstream regions (e.g., Chen et al, 2022; Watanabe, 2004; Wu et al, 2011). Some recent works have found that the interdecadal transition in the phase of the North Atlantic‐related Eurasia (EU) pattern during the late 1980s plays a primary role in the interdecadal changes of moisture transportation, which in turn, contribute to the increased precipitation over northwest China after the late 1980s (Yin & Zhou, 2022; Zhou & Wu, 2015). The contemporaneous anomalous SSTs over the North Atlantic associated with the PIhf were examined for both P1 and P2 (Figure 6a,b).…”
Section: The Sptb Variations Related Ocean–atmosphere Anomaliesmentioning
confidence: 99%